ER-α36 Promotes the Malignant Progression of Cervical Cancer Mediated by Estrogen via HMGA2 - Wang, Chunyan; Zhang, Tianli; Wang, Kun; Zhang, Shuo; Sun, Qing; Yang, Xingsheng (Frontiers in Oncology, 2021)
Objectives: Estrogen is proven to promote the malignant behaviors of many cancers via its receptors. Estrogen receptor alfa 36 (ER-α36) is a newly identified isoform of estrogen receptor alfa (ER-α), the role of ER-α36 in regulating the effects of estrogen and its potential impact on human cervical cancer is poorly understood. Methods: Immunohistochemistry staining was used to evaluate the expression of ER-α36, estrogen receptor alfa 66 (ER-α66) and their prognostic values in cervical cancer. The effects of ER-α36 and ER-α66 on the proliferation and metastasis of cervical cancer were measured in vitro. A xenograft tumor assay was used to study the tumorigenesis role of ER-α36 in vivo. Furthermore, the functional gene at the downstream of ER-α36 was obtained via next-generation sequencing, and the biological functions of high mobility group A2 (HMGA2) in cervical cancer cells were investigated in vitro. Results: ER-α36 was over-expressed in cervical cancer tissues and elevated ER-α36 expression was associated with poor prognosis in cervical cancer patients. High expression of ER-α36 promoted the proliferation, invasion and metastasis of cervical cancer cells mediated by estrogen, while silencing ER-α36 had the opposite effects. Further research showed that HMGA2 was a downstream target of ER-α36 in cervical cancer cells. The oncogenic effect of ER-α36 was attenuated after HMGA2 knockdown. Conclusions: High expression of ER-α36 was correlated with a poor prognosis in cervical cancer by regulating HMGA2. ER-α36 could be a prognostic biomarker and a target for cervical cancer treatment.